Targeting DNA-dependent protein kinase sensitizes hepatocellular carcinoma cells to proton beam irradiation through apoptosis induction - Choi, Changhoon (PLoS One, 2019)
Recent studies have highlighted the implications of genetic variations in the relative biological effectiveness (RBE) of proton beam irradiation over conventional X-ray irradiation. Proton beam radiotherapy is a reasonable radiotherapy option for hepatocellular carcinoma (HCC), but the impact of genetic difference on the HCC RBE remains unknown. Here, we determined proton RBE in human HCC cells by exposing them to various doses of either 6-MV X-rays or 230-MeV proton beams. Clonogenic survival assay revealed variable radiosensitivity of human HCC cell lines with survival fraction at 2 Gy ranging from 0.38 to 0.83 and variable proton RBEs with 37% survival fraction ranging from 1.00 to 1.48. HCC cells appeared more sensitive to proton irradiation than X-rays, with more persistent activation of DNA damage repair proteins over time. Depletion of a DNA damage repair gene, DNA-PKcs, by siRNA dramatically increased the sensitivity of HCC cells to proton beams with a decrease in colony survival and an increase in apoptosis. Our findings suggest that there are large variations in proton RBE in HCC cells despite the use of a constant RBE of 1.1 in the clinic and targeting DNA-PKcs in combination with proton beam therapy may be a promising regimen for treating HCC.